2013
DOI: 10.1186/1476-0711-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of bacteria and candida using pna-fish from blood and peritoneal fluid cultures: a retrospective clinical study

Abstract: BackgroundPeptide nucleic acid fluorescent in situ hybridization (PNA-FISH) is a rapid and established method for identification of Candida sp., Gram positive, and Gram negative bacteria from positive blood cultures. This study reports clinical experience in the evaluation of 103 positive blood cultures and 17 positive peritoneal fluid cultures from 120 patients using PNA-FISH. Our study provides evidence as to potential pharmaceutical cost savings based on rapid pathogen identification, in addition to the nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 17 publications
(24 reference statements)
0
32
0
3
Order By: Relevance
“…The newer QuickFISH test identifies the three most commonly encountered species: C. albicans, C. glabrata, and C. parapsilosis. PNA FISH tests have demonstrated costsavings by reducing echinocandin use for fluconazole-susceptible species in several reports [12,39].…”
Section: Pna Fishmentioning
confidence: 98%
“…The newer QuickFISH test identifies the three most commonly encountered species: C. albicans, C. glabrata, and C. parapsilosis. PNA FISH tests have demonstrated costsavings by reducing echinocandin use for fluconazole-susceptible species in several reports [12,39].…”
Section: Pna Fishmentioning
confidence: 98%
“…These assays have been shown to have excellent analytical performance. [10][11][12][13] Given the emergent nature of bloodstream infections, rapid blood culture diagnostic methods may be one of the most important tests a clinical microbiology laboratory could implement. Indeed, several studies have shown that the use of these assays can improve patient care.…”
Section: Diagnostic Tests Performed On Positive Blood Culture Specimensmentioning
confidence: 99%
“…In the clinical laboratory, counterinsurgency intelligence gathering would require new technology, a new electronic health record, and a new mindset. Various technologies for community characterization are already available -particularly high-throughput sequencing (Xu et al 2012), but also multiplexed PCR Hartley 2003, Lindsay et al 2013), hybridization arrays (Gardner et al 2010), microfluidic culture (Ho et al 2012), flow cytometry (Jolkkonen et al 2010, Nuutila et al 2012, and novel approaches to microscopy (Foreman et al 2010, Harris et al 2013. Each has limitations and none of them provide quite what would be desired to understand the function of a microbial community de novo.…”
Section: Intelligencementioning
confidence: 99%